Smoking prevalence and associated risk factors among healthcare professionals in Nicosia general hospital, Cyprus: A cross-sectional study - Zinonos, Stavri; Zachariadou, Theodora; Zannetos, Savvas; Panayiotou, Andrie; Georgiou, Andreas (My University, 2016)
Background: In recent years, a significant progress has been achieved globally in reduction of smoking among physicians and nurses, however, in some countries the smoking prevalence of health professionals is maintained at very high levels, without significant difference from the general population. This study aims to investigate the prevalence of smoking among physicians and nurses working at Nicosia General Hospital, as well as their knowledge and attitudes towards smoking cessation strategies. Methods: This is a cross-sectional questionnaire-based study. The study consisted of 119 doctors and 392 nurses currently working at Nicosia General Hospital in Cyprus. Study participants were recruited from all hospital wards between May and June 2008. Both physicians and nurses were asked to answer an anonymous questionnaire, which included questions regarding their smoking habits, knowledge and attitudes about smoking and smoking cessation strategies. Results: Overall smoking prevalence among healthcare professionals was 28.2 % (28.6 % among physicians and 28.1 % among nurses). Multivariate analysis revealed that being male, younger than 34 years old, unmarried and with a family history of smoking were associated with increased likelihood of being a current smoker. An impressive 72 % of current smokers reported that they wished to quit smoking, however, only 5.6 % of physicians and 6.9 % of nurses, reported ever using any smoking cessation aids. Never- smokers counseled their patients to quit smoking more often (96.4 %) compared to former (84.6 %) and current smokers (72.7 %), (p < 0.001). In addition, those who felt more confident about their knowledge regarding smoking cessation, reported counseling their patients to quit smoking more often compared to those who did not (92 % vs 60 %, p < 0.001). Conclusions: Smoking prevalence among physicians and nurses working at Nicosia General Hospital was similar to that of the general Cypriot population. Further training of healthcare professionals towards smoking cessation strategies is needed in order to improve their knowledge and consequently their efforts on counseling and support to their patients who wish to quit smoking.
Keywords: Healthcare professionals; Smoking attitudes; Smoking prevalence